Implementasi Sistem Informasi dalam Meningkatkan Mutu Layanan Pendidikan di Sekolah Menengah Pertama Negeri 6 Topoyo - Hilal Mahmud; Aishiyah Saputri Laswi; , Baderiah; Tasdin Tahrim; M. Surya Renaldi (Journal of Cross Knowledge, 2024)
This research aims to: To determine the quality of education at SMP Negeri 6 Topoyo; To find out the application of information systems in improving the quality of educational services at SMP Negeri 6 Topoyo and Obstacles to the application of information systems in improving the quality of educational services at SMP Negeri 6 Topoyo. The type of research used is descriptive qualitative. The subjects of this study were principals, teachers, administrative staff, and school operators. Research data were obtained through interviews, observations, and documentation studies. The data analysis technique uses raw data collection, data condensation, data presentation, and conclusions. The results of this study show that; (1) The quality of administrative services is inadequate due to lack of coordination and communication between staff. The learning process service has been running well supported by the use of information systems in learning planning and implementation.(2) The application of SI in improving the quality of education services can be seen in administrative services through the Dapodik application. In addition, in the process of learning. The application of SI can be seen by the use of e-learning systems.(3) Obstacles to the implementation of SI in improving the quality of education services can be seen in administrative services through network stability. Meanwhile, in the learning process of implementing SI, it can be seen from that there are still students who experience unstable networks, run out of internet quota, and forget account passwords.